A machine learning, artificial intelligence approach to institutional effectiveness in higher education - Moye, John N. (Emerald, 2019)
The Institutional Research profession is currently experimenting with many strategies to assess institutional effectiveness in a manner that reflects the letter and spirit of their unique mission, vision, and values. While a 'best-practices' approach to the measurement and assessment of institutional functions is prevalent in the literature, a machine learning approach that synthesises these parts into a coherent and synergistic approach has not emerged. This book presents a practical, effective, and systematic approach to the measurement, assessment, and sensemaking of institutional performance.